Eruption and emplacement timescales of ignimbrite super-eruptions from thermo-kinetics of glass shards - Lavallée, Yan; Wadsworth, Fabian B.; Vasseur, Jérémie; Russell, James K.; Andrews, Graham D. M.; Hess, Kai-Uwe; von Aulock, Felix W.; Kendrick, Jackie E.; Tuffen, Hugh; Biggin, Andrew J.; Dingwell, Donald B. (Frontiers in Earth Science, 2015)
Super-eruptions generating hundreds of cubic kilometres of pyroclastic density currents are commonly recorded by thick, welded and lava-like ignimbrites. Despite the huge environmental impact inferred for this type of eruption, little is yet known about the timescales of deposition and post-depositional flow. Without these timescales, the critical question of the duration of any environmental impact, and the ensuing gravity of its effects for the Earth system, eludes us. The eruption and welding of ignimbrites requires three transects of the glass transition. Magma needs to: 1) fragment during ascent, 2) liquefy and relax during deposition, agglutination and welding (sintering), and 3) quench by cooling into the glassy state. Here we show that welding is a rapid, syn-depositional process and that the welded ignimbrite sheet may flow for up to a few hours before passing through the glass transition a final time. Geospeedometry reveals that the basal vitrophyre of the Grey’s Landing ignimbrite underwent the glass transition at a rate of ~0.1 °C.min^-1 at 870 °C; that is, 30-180 °C below pre-eruptive geothermometric estimates. Application of a 1-D cooling model constrains the timescale of deposition, agglutination, and welding of the basal vitrophyre to less than 1 hour, and possibly even tens of minutes. Thermo-mechanical iteration of the sintering process indicates an optimal temperature solution for the emplacement of the vitrophyres at 966 °C. The vitrophyres reveal a Newtonian rheology up to 46 MPa, which suggests that the ash particles annealed entirely during welding and that viscous energy dissipation is unlikely from loading conditions alone, unless shear stresses imposed by the overlying ash flow were excessively high and sustained over long distances. The findings underline the value of the term 'lava-like' flow to describe the end rheology of Snake River-type ignimbrites, fully consistent with the typical lithofacies observed.